IMPLEMENTASI NILAI - NILAI PLURALISME BERDASARKAN NILAI-NILAI BUDAYA BANGSA - Mantik, Aliyah (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2016)
Pluralism is the term which it has many difference meaning. At the same time, someone can accept and refuse pluralism according to that meaning. Secular humanism argues that there is no an Absolute Truth, because the truth is depend on human. The truth is subjective and relative, so unity just can be built by secularism. Global theology offers a new  theology  that  is  global  theology  to  unite  the  difference  religions.  Syncretism selected and mixed religions become a new religion. Perennial Philosophy tries to find meeting is understood as a framework of interaction in which groups show point of religions in the esoteric area. In the social sciences, pluralism sufficient respect and tolerance of each other, that they fruitfully coexist and interact without conflict or assimilation. Pluralism as theory is a social construction. Indonesian can construct pluralism base on the values of Pancasila that are Goddess, humanity, unity, democracy and justice.